2015
DOI: 10.1093/ajh/hpv134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antihypertensive Agents on Central Systolic Blood Pressure and Augmentation Index: A Meta-Analysis

Abstract: Elevated blood pressure (BP) is a leading modifiable risk factor for cardiovascular disease and continues to affect approximately 1 in 3 adults, or 66.9 million people, in the United States. 1 Traditionally, hypertension is diagnosed and treated by assessing the pressure at the brachial artery (peripheral BP), 2 but recent evidence suggests that central hemodynamics are better predictors of cardiovascular outcomes and mortality. 3,4 Central BP is indicative of the pressure directly exerted on target organs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 96 publications
4
27
1
2
Order By: Relevance
“…New evidence suggests that central SBP is a better predictor of adverse CV outcomes than peripheral SBP [36]. It has also been shown that thiazide diuretics reduce central SBP and peripheral SBP in a similar manner [36], and with results comparable to what is observed with other antihypertensive agents [37].…”
Section: Thiazide-like Diuretics In T2d Patients With Hypertensionmentioning
confidence: 91%
“…New evidence suggests that central SBP is a better predictor of adverse CV outcomes than peripheral SBP [36]. It has also been shown that thiazide diuretics reduce central SBP and peripheral SBP in a similar manner [36], and with results comparable to what is observed with other antihypertensive agents [37].…”
Section: Thiazide-like Diuretics In T2d Patients With Hypertensionmentioning
confidence: 91%
“…Overall, it appears that beta-blockers reduce central blood pressure signifi cantly less than brachial blood pressure [59]. In contrast, the other drug classes signifi cantly decrease central blood pressure, although the extent to which this is independent of their brachial blood pressurelowering eff ect is still debated.…”
Section: Do Some Drug Classes Have More Benefi Cial Effects On Centramentioning
confidence: 99%
“…In contrast, the other drug classes signifi cantly decrease central blood pressure, although the extent to which this is independent of their brachial blood pressurelowering eff ect is still debated. A recent meta-analysis showed that most antihypertensive drug classes, including alpha-blockers, angiotensin-converting enzyme inhibitors (ACEis), angiotensin receptor blockers (ARBs), calcium channel blockers (CCBs), renin inhibitors and thiazides, may reduce peripheral and central pressure to the same extent and confi rmed the lack of effi cacy of beta-blockers in lowering central compared with brachial blood pressure [59]. A further meta-analysis of 24 randomised clinical trials [60] suggested that beta-blockers and diuretics reduce central pressure less than brachial pressure, whereas monotherapy with ACEis, ARBs, CCBs, alpha-blockers or spironolactone reduced both parameters to a similar extent [60].…”
Section: Do Some Drug Classes Have More Benefi Cial Effects On Centramentioning
confidence: 99%
See 2 more Smart Citations